AGAINST THE MARKET: LOCAL COMMUNITIES AND POLANYIAN CONTENTION IN INDIA AND TURKEY. - GEMICI, KURTULUŞ; NAIR, MANJUSHA (Journal of Global South Studies)
The widening reach of neoliberal reforms, global production chains, and market relations has been displacing the means of livelihood for many social groups around the world. In contrast to what the proponents of globalization contend, such displacements have jeopardized the livelihood of social groups that were sidelined by market-friendly reforms. A large body of scholarship suggests that such conditions are likely to generate popular protest against the spread of market relations. In this article, we examine the conditions under which the social groups that have been unmade by the spread of the market economy mobilize against the market. Drawing on the literature of the moral economy and the study of contentious politics, we emphasize that the connective structures social relations provide are crucial in turning economic and moral grievances against the market into collective mobilization. We argue that the social relations embodied in the communities that are threatened by the spread of capitalism and market relations form strong bases of collective action. We illustrate this argument with instances of contentious politics in India and Turkey.